(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
Pure and Ni doped TiO2 thin films are prepared by sol-gel dip coating technique and sintered at 500 oC. Particle size decreases from 40 nm to 20 nm in case of 10 mol% Ni doped TiO2 thin films. XPS studies reveal that titanium exists in Ti+4 state in pure and Ni doped TiO2 thin films. MOS structure are formed by fabricating the ITO bottom electrode and Al top electrode. The thickness of all the Ni doped TiO2 thin films is nearly 140 nm as measured by thickness profill ometer. Dielectric constant and dielectric loss decreases with increase in frequency. Anatase phase has been found in pure and Ni doped TiO2 thin films. Density of interfacial states measured with the help of measured values of capacitances.